In vivo application of Oreochromis niloticus scales collagen as alternative wound healing therapy - Abdul Ghafar, Ainul Shafikah; Wahab, Mohd Shazwan Shazdee; Ismail, Elysha Nur; Ishak, Reezal (Journal of Medical Pharmaceutical and Allied Sciences, 2022)
Fish collagen derived from its skins, scales or bones are known to have many advantages in medical and pharmaceutical applications. This study evaluates the effectiveness of collagen extracted from the scales of local Malaysian Oreochromis niloticus or red Nile tilapia fish, on wound healing in an animal model. 21 male BALB/c mice were divided into three different groups namely the control group, Oreochromis niloticus acid-solubilized collagen extracts treated group; and acriflavine treated group. A full thickness surgical wound of about 1.5 cm were inflicted on the dorsal area of the animal. Treatment with collagen extracts and acriflavine were applied daily on the wounds and measured every day for 9 days. The mice were randomly sacrificed on day 3, 6, and 9, and the skin samples were taken for histological assessment. After 3 days, treatment with collagen extracts and acriflavine recorded an average wound measurement of 7.84±0.32 mm and 7.14±0.32, respectively. On day 9, the progress of wound healing showed significant differences. Mice treated with collagen extracts recorded an average wound measurement of 1.27±0.08 mm, as compared to 3.26±0.05 mm of acriflavine treated, and 3.36±0.18 mm of the control group. The wound assessment showed that collagen extracted from the scales of local Oreochromis niloticus fish produced significant results based on the skin re-epithelialization process and formation of new blood vessels. This finding indicates that collagen extracted from the local Oreochromis niloticus scales possessed effective wound healing properties for surgical wounds as demonstrated on the skin of the animal model.